OP0269 Detection of Synovitis in Clinically Inactive Juvenile Idiopathic Arthritis Patients by Ultrasonography with Power Doppler. (23rd January 2014) - Collado, P.; Gamir, M. L.; Merino, R.; Modesto, C.; Monteagudo, I.; Lopez-Robledillo, J. C.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of arthritides that all present with chronic joint inflammation that can lead to structural damage. The advances in therapeutic effectiveness have created a need for looking for imaging tools that describe more precisely the clinical state of disease inactivity. The well-known advantages of ultrasonography with power Doppler (PDUS) makes that this technique is ideal for evaluation of the pediatric population in the clinical setting and lets clinicians choose an appropriate treatment to induce remission. Objectives: The purpose of this study was to determine the prevalence of abnormalities detected by ultrasonography (US) in JIA patients presenting clinically inactive disease (ID) –on medication and off medication – and to compare between two groups. Methods: Study design: Cross-sectional, multicenter study. Patients: Inclusion criteria: 1) JIA patients, age from 4 to 16 years old, 2) remission according to clinical assessment by their consultant doctor for a minimum of 6 months prior to the screening, 3) taking stable disease modified anti-rheumatic drugs (DMARDs) therapy or have discontinued medications for JIA for a minimum of 6 months, 4) biologics naïve patients. Exclusion criteria: Intra-articular steroid injection in the last 6 months. Data collected: Clinical and PDUS assessments were performed blindly on 44 joints. Other clinical and laboratory markers of activity disease were collected. For the analysis the Outcome Measure in Rheumatology in Clinical Trials (OMERACT) definitions for rheumatoid arthritis of synovitis and tenosynovitis were applied in our patients. The presence of Doppler signal inside the intraarticular synovium or in the synovial sheath was considered as inflammatory activity. Results: 34 patients, of whom 23 patients have attained clinical remission on medication (CRM) with DMARD therapy and 11 patients have attained inactivity disease off medication (CR) (1 ). The mean (SD) disease duration was 48 (35) months. Half of the study patients have attained one or more previous inactivity disease state, but there was no significant difference between the 2 groups. Thirteen (38.2%) patients had evidence of ≥1 US findings, although the number of US abnormalities detected in CRM patients was higher than CR group, there were no significant differences between the 2 groups in detecting GS synovitis (p=0.86) and PD signal (p=0.38). US examination showed 37 joints presented GS synovial hypertrophy and 18 (48 %) of 37 joints with GS synovitis presented increased PD signal. Conclusions: Our study shows that a proportion of patients presenting clinically inactive disease presented GS synovitis and some of them seem to present inflammatory activity detected by PDUS. The significance of these findings has importance in order to obtain an accurate definition of disease status in the growing skeleton of JIA patients. References: Wallace CA, Ruperto N, Giannini EH. Preliminary criteria for clinical remission for select categories of juvenile idiopathic arthritis. J Rheumatol 2004; 31:2290-4 Disclosure of Interest: P. Collado Grant/research support from: Pfiser, M. L. Gamir Grant/research support from: Pfiser, R. Merino Grant/research support from: Pfiser, C. Modesto Grant/research support from: Pfiser, I. Monteagudo Grant/research support from: Pfiser, J. C. Lopez-Robledillo Grant/research support from: Pfiser